Gene Regulation of Intestinal Porcine Epithelial Cells IPEC-J2 Is Dependent on the Site of Deoxynivalenol Toxicological Action - Diesing, Anne-Kathrin (Public Library of Science, 2012)
The intestinal epithelial cell layer represents the border between the luminal and systemic side of the gut. The decision between absorption and exclusion of substances is the quintessential function of the gut and varies along the gut axis. Consequently, potentially toxic substances may reach the basolateral domain of the epithelial cell layer via blood stream. The mycotoxin deoxynivalenol (DON) is a Fusarium derived secondary metabolite known to enter the blood stream and displaying a striking toxicity on the basolateral side of polarised epithelial cell layers in vitro. Here we analysed potential mechanisms of apical and basolateral DON toxicity reflected in the gene expression. We used the jejunum-derived, polarised intestinal porcine epithelial cell line IPEC-J2 as an in vitro cell culture model. Luminal and systemic DON challenge of the epithelial cell layer was mimicked by a DON application from the apical or basolateral compartment of membrane inserts for 72 h. We compared the genome-wide gene expression of untreated and DON-treated IPEC-J2 cells with the GeneChip® Porcine Genome Array of Affymetrix. Low basolateral DON (200 ng/mL) application triggered 10 times more gene transcripts in comparison to the corresponding apical application (2539 versus 267) despite the intactness of the challenged cell layer as measured by transepithelial electrical resistance. Analysis of the regulated genes by bioinformatic resource DAVID identified several groups of biochemical pathways modulated by concentration and orientation of DON application. Selected genes representing pathways of the cellular metabolism, information processing and structural design were analysed in detail by quantitative PCR. Our findings clearly show that apical and basolateral challenge of epithelial cell layers trigger different gene response profiles paralleled with a higher susceptibility towards basolateral challenge. The evaluation of toxicological potentials of mycotoxins should take this difference in gene regulation dependent on route of application into account.